EP-573 Does type of surgery influence recurrence of breast cancer in younger patients?. (9th August 2022) - Farrugia, Alexia; Green, Matt; Brookes, Phil; Kasana, Iqbal
Abstract: It is well established that young age is a risk factor for outcome of breast cancer, and younger women are more likely to have adverse prognostic factors. Our aim was to investigate whether type of surgery (wide local excision vs mastectomy) had any effect on local or distant recurrence in women under the age of 35. All women with breast cancer under the age of 35 treated between 1st January 2010 and 31st December 2020 were included. Data including age at diagnosis, comorbidities, type of surgery, neoadjuvant/adjuvant treatment, histology, lymph node positivity, expression of receptors, local/distant recurrence was collected. There were 34 patients included, age range 21–34. Ten patients had a wide local excision (WLE) while the rest had a mastectomy. Four patients had local recurrence while nine patients had distal recurrence. In WLE group 1 out of 10 had local recurrence and 2 out of 10 had distant metastasis (one of these patients had both). In mastectomy group 2 out of 24 had local recurrence and 7 out of 24 had distant metastasis (two patients had both). The average recurrence time was 1.7 years after initial diagnosis. Using a Chi-square test, there was no significant difference found for local, distant or overall recurrence between patients having wide local excision or mastectomy (p=0.719, p=0.554, p=0.462 respectively). Type of surgery did not affect the local or distant recurrence rate. The sample size is small, and a larger series is required to determine whether it is equally safer to offer WLE to younger women.